Characterization of Oncolytic Herpesviruses - Rodrigues, Rebecca (My University, 2008)
Oncolytic viruses are able to selectively replicate in tumour cells and are an attractive new avenue of cancer therapy that lacks the toxic side effects of current treatment modalities. HSV-1 mutants lacking ICPO are promising oncolytic vectors, however, the mechanisms behind viral oncolysis remain unclear. Since PML contributes to the repression of HSV-1 and also is downregulated in various types of cancer, but particularly in prostate cancer, PML has been implicated as a factor influencing the permissiveness of tumour cells to I CPO-null HSV-1 oncolysis. By screening a series of immortalized patient matched normal and tumour prostate epithelial cells for sensitivity to ICPO-null HSV-1 oncolysis and evaluating the levels of PML in each cell line, we were unable to establish a link between PML status and permissiveness to ICPO-null HSV-1 oncolytic vectors. Also, since a large proportion of the population possesses pre-existing immunity to HSV -1, which may hinder systemic administration of HSV-1 vectors, we sought to determine if BHV-1 could be an alternative oncolytic herpesvirus. BHV-1 was cytotoxic to various human immortalized and transformed cell lines in vitro, but was generally more restricted from normal human cells, suggesting that BHV -1 may have potential as an oncolytic virus. However, the sensitivity of human cells to BHV -1 infection did not correlate with type I IFN signaling, as has been demonstrated for other oncolytic viruses. Furthermore, neutralizing antibodies against HSV-1 were unable to cross-react with BHV -1 in vitro suggesting that pre-existing immunity to HSV -1 in humans may not hinder BHV -1 infection. It is hoped that these results will contribute to the understanding of viral mediated oncolysis and also provide some evidence that BHV-1 may be a new alternative oncolytic herpesvirus, however, in vivo studies are necessary to evaluate the oncolytic efficacy of BHV -1.
Keywords: Oncolytic; Herpesviruses; tumour cells; viral oncolysis